Job control and the risk of incident stroke in the working population in Sweden - Toivanen, Susanna (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study estimated the risk of incident stroke according to the level of job control and examined whether the association between job control and the risk of stroke varied as a function of gender. ' ' METHODS ': 'This was a register-based cohort study of nearly 3 million working people (age 30–64 years in 1990) with a 13-year follow-up (1991–2003) for incident stroke (50 114 events). Job control was aggregated to the data by a secondary data source (job-exposure matrix) in 1990. Gender-specific Cox regressions were applied. ' ' RESULTS ': 'The age- and workhour-adjusted hazard ratio of the lowest versus the highest job control quartile was 1.25 [95% confidence interval (95% CI) 1.17–1.32] for any stroke, 1.33 (95% CI 1.15–1.55) for intracerebral hemorrhage, and 1.22 (95% CI 1.14–1.31) for brain infarction among the women, and the corresponding figures for the men were 1.24 (95% CI 1.21–1.28), 1.30 (95% CI 1.21–1.40), 1.23 (95% CI 1.19–1.28), respectively. Adjustment for education, marital status, and income attenuated these associations to 1.07 (95% CI 1.01–1.14) for any stroke, 1.22 (95% CI 1.04–1.42) for intracerebral hemorrhage, and 1.04 (95% CI 0.97–1.12) for brain infarction for the women and to 1.08 (95% CI 1.04–1.12), 1.12 (95% CI 1.03–1.22), 1.08 (95% CI 1.04–1.13), respectively, for the men. ' ' CONCLUSIONS ': 'The relative risk of stroke was higher in low job-control occupations. The association between job control and stroke subtypes varied as a function of gender. The relative risk of intracerebral hemorrhage was highest for the women in low job-control occupations.
Keywords: cohort study; incident stroke; job control; job-exposure matrix; occupational epidemiology; risk; stroke; Sweden; working population